Emerging realm of 360-degree technology to promote tourism destination - Rahimizhian, Sima; Ozturen, Ali; Ilkan, Mustafa (Elsevier Sci Ltd, 2020)
Emerging technologies are leading the travel industry to vital changes. The use of 360-degree videos in marketing plans allows destination marketers to give their customers a virtual adventure before their actual trip. By integrating the motivation theory and Technology Acceptance Model (TAM), a research model was extended to investigate whether 360-degree videos are influential in producing a more positive attitude and shaping consumers' behavioral intentions towards a destination. Structural equation modeling (SEM) was applied to test the relationships between the proposed constructs. Data was collected from European respondents (n = 598) via an online survey regarding Hong Kong as a tourist destination. The results revealed that both intrinsic and extrinsic motivators influence tourists' satisfaction with a 360-degree experience of the destination that indirectly affects their visit and electronic word of mouth (eWOM) intentions through behavioral involvement. Overall, the findings reflected that a 360-degree video is a beneficial tool in attracting consumers and shaping their attitudes and intentions. The theoretical and managerial implications of findings, as well as recommendations for future research, are addressed.
Keywords: 360-Degree video; Technology acceptance; Virtual experience; Intrinsic and extrinsic motivators; TAM